Avaliação da composição corporal e qualidade de vida em pacientes submetidos ao esvaziamento cervical supraomohióideo - PAULA JÚNIOR, Célio Antônio de (2012)
Supraomohyoid neck dissection is an important procedure in the treatment of patients with malignancy in the oral cavity and oropharynx, however there are common side effects in the post operative period. Results of an elaborate review of literature in electronic databases to investigate the effect of a resistance exercise protocol in this population showed significant improvement in the quality of life of patients trained, however studies which deal with the issue are limited. To quantify the damage caused by post-operative supraomohyoid neck dissection, and thus develop a secure protocol of exercises for this population, this study evaluated changes in body composition, body mass index, range of motion and quality of life in patients undergoing unilateral or bilateral supraomohyoid neck dissection pre and post-operatively (30 and 90 days). In the post-operative period, the 28 patients observed showed a significant reduction in body weight, muscle weight, and fat percentage. In terms of range of motion, a reduction of flexion, extension, abduction, medial rotation and lateral rotation was detected in the post-operative period (30 and 90 days). Decreased range of motion of flexion and abduction post-operatively had a negative correlation with quality of life, especially in areas of activity, recreation, shoulder, and the total score. The results of this study indicate that a resistance exercise protocol in patients undergoing neck dissection supraomohyoid may be an alternative to reduce the adverse effects of surgery and thus improve quality of life of these patients.